Splatoon. Vol. 8 - Hinodeya, Sankichi; Hurley, Jason A., 1981- (VIZ Media, LLC, 2020)
The hour of the Splatfest has arrived, a Turf War where teams of Inklings split up their players to face off against each other. Team Blue splits into "funny Man" and "Straight Man" teams, but who will face who is another matter. Includes a short story with Splattershot Jr.